Effect of Methylphenidate on State Anxiety in Children With ADHD-A Single Dose, Placebo Controlled, Crossover Study - Kritchman, Maya; Koubi, May; Mimouni Bloch, Aviva; Bloch, Yuval (Frontiers in Behavioral Neuroscience, 2019)
Introduction: Non-adherence to efficacious pharmacotherapy is a major obstacle in the treatment of children suffering from attention deficit hyperactive disorder (ADHD). Some hold the position that pharmacotherapy induces anxiety, and that this is one of the reasons for this non-adherence. Previous studies have pointed to the opposite, a moderating effect of methylphenidate (MPH) on state anxiety in patients with ADHD. This has been shown in continuous treatment in children, but not on a single dose. We hypothesized that a single dose might have a different effect. Method: Twenty children with ADHD were given single doses of MPH in a randomized, controlled, crossover, double blind study. State anxiety using The Spielberger State-Trait Anxiety Inventory (STAI) and a continuous performance test were assessed. Results: As a group, no change was detected in state anxiety with MPH or placebo. However, children who were given MPH during the first session as opposed to those who received placebo first, demonstrated deterioration in baseline state anxiety in the second session (t(2.485) , p<0.05). Conclusion: Our findings show a possible delayed anxiety-provoking effect of a single dose of MPH. This may be relevant to the understanding of difficulties in adherence with MPH treatment in children with ADHD.